“Academic Work Syndrome” (SINATA) in educational institutions in Latin America - Herrera Mijangos, Santos Noé; Luna Reyes, Dayana; Escobar Torres, Jorge Gonzalo (Education Policy Analysis Archives, 2019)
The objective of this research was to describe the internal-external context of select educational institutions as well as the biological, psychological and social status of teachers and researchers. The work is based on qualitative and quantitative methodology. The population that has been considered covers Mexico and Colombia, although it also includes Chile and Argentina because research was done in those Latin American countries. The subjects of analysis were found in both public and private educational institutions, from basic to postgraduate level. Qualitatively, interviews and ethnographic work were carried out. Quantitatively, the scale of the “Academic Work Syndrome” (SINATA) was used, which aims to investigate the burdens of teaching. The results showed that due the internal-external context of their educational institutions, the academics spend a great part of their time satisfying the demands of the dominant educational trend, and that the internal political divisions and in-fighting generates the majority of SINATA that the teachers suffer. It should be noted that the results coincide with those reported in Chile and Argentina. Teacher suffering affects educational quality, a dependent and conditioned variable for the physical and mental health of the teacher.